Transdermal glyceryl trinitrate (nitroglycerin) in healthy persons: acute effects on skin temperature and hemodynamic orthostatic response - Haebisch, Eva Maria Augusta Boeckh (São Paulo Medical Journal, 1995)
In order to find an explanation for individual reactions to transdermal glyceryl trinitrate (GTN) we studied the skin temperature and hemodynamic reactions in 63 healthy persons. The data were obtained before and after the application of GTN and Glycerin (GL) placebo patches, during one hour. The skin temperature was measured on both forearms, the local (left sided) and systemic (right sided) reaction on GTN was related to the skin fold and the calculated body fat content. The bilateral rise of skin temperature and its duration was higher and longer in obese than in lean persons mainly in obese women. The UV induced thermo and the later photothermoreaction (Erythema) was reduced on the left forearm after the application of GTN and GL patches. The observed hemodynamic GTN effect confirmed known postural reactions, such as decreased arterial pressure (ΔmAP = -2.9%), increased heart rate (ΔHR = +7,4%) and QTc prolongation (ΔQTc = +4,9%) in upright position. An adverse drug effect with increased mean blood pressure (ΔmAP = +12%) and increased heart rate (ΔHR = + 10.4%) mainly in supine position was observed in 11 % of the participants, but only in men. Such a reaction was already described by Murell, 1879. Individual GTN effects were analyzed and related to habits and family history. In male smokers and in persons with hypertensive and diabetic close relatives, the hypotensive GTN effect was accentuated in supine position. In the upright position the group with hypertensives in the family presented a moderate hypotensive reaction without secondary tachycardia and the smokers presented only a slightly increased heart rate. Our observations suggest that individual reactions to transdermal glyceryl trinitrate (GTN) with its active component nitric oxide (NO) depends on physiological conditions, related to endogenous vasoactive substances, mainly the interaction with EDRF (the endogenous NO) and the activity of the Renin-Angiotensin System.